2002
DOI: 10.1038/sj.bjp.0704808
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen attenuates oxidative stress‐induced apoptosis via the inhibition of the c‐Jun N‐terminal kinase and activator protein‐1 signalling pathway in PC12 cells

Abstract: 1 Ebselen (2-phenyl-1,2-benzisoselenazol-3[2H]-one) is a selenoorganic compound exhibiting both glutathione peroxidase activity and antioxidant activity. Although it has been reported that ebselen is e ective for oxidative stress-induced neuronal damage both in vivo and clinically, the precise mechanisms of the e cacy have not yet been elucidated. Thus, we hypothesized that ebselen may a ect reactive oxygen species-induced mitogen-activated protein (MAP) kinase activation in cultured PC12 cells. 2 Our ®ndings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 51 publications
4
44
0
Order By: Relevance
“…Exogenous H 2 O 2 has been shown to activate all three types of MAPK in many cell types, including HeLa cells (4,18,(45)(46)(47)(48)(49)(50). We have also confirmed the activation of all three types of MAPK in HeLa cells by exogenous H 2 O 2 (data not shown).…”
Section: Effects Of Prx Ii(wt) and Prx Ii(dn) On Tnf-␣-induced Ask1supporting
confidence: 61%
“…Exogenous H 2 O 2 has been shown to activate all three types of MAPK in many cell types, including HeLa cells (4,18,(45)(46)(47)(48)(49)(50). We have also confirmed the activation of all three types of MAPK in HeLa cells by exogenous H 2 O 2 (data not shown).…”
Section: Effects Of Prx Ii(wt) and Prx Ii(dn) On Tnf-␣-induced Ask1supporting
confidence: 61%
“…Conversely, the 30 mg/kg dose of ebselen significantly increased the apoptotic index. Our results were consistent with previous studies [30,[33][34][35][36]. Yang et al demonstrated that ebselen led to a dose-dependent increase of TUNEL-positive cells, which depleted intracellular glutathione (GSH) and protein thiols [35].…”
Section: Discussionsupporting
confidence: 93%
“…However, HGECs treated with Ang II and 90% Tf for 6 h showed 1:2:2:1 quartet EPR signals with hyperfine coupling constants of a N ¼a H ¼1.49 mT (Figure 5d), which were consistent with the reported values for the DMPO/ OH spin adduct. 38,42 These findings indicated that Ang II and 90% Tf facilitated OH generation in HGECs.…”
Section: Epr Measurements Of Ang II and 90% Tf-induced Dmpo/ Oh Genermentioning
confidence: 76%
“…38 HGECs were seeded (1Â10 5 cells cm À2 ) and grown to subconfluence in 60-mm culture dishes in CSC growth medium-10% fetal bovine serum. Cells were pretreated with or without 90% Tf (50 mM) for 5 min, then treated with or without Ang II (1 nM) for 6 h at 37 1C, and then cells were washed twice with PBS.…”
Section: Electron Paramagnetic Resonance (Epr) Measurements Of Ros Gementioning
confidence: 99%